Cardiopulmonary fitness predicts postoperative major morbidity after esophagectomy for patients with cancer. Issue 14 (24th July 2019) - Patel, Neil; Powell, Arfon G.; Wheat, Jenni R.; Brown, Christopher; Appadurai, Ian R.; Davies, Richard G.; Bailey, Damian M.; Lewis, Wyn G.
Abstract: Surgery for radical treatment of esophageal cancer (EC) carries significant inherent risk. The objective identification of patients who are at high risk of complications is of importance. In this study the prognostic value of cardiopulmonary fitness variables (CPF) derived from cardiopulmonary exercise testing (CPET) was assessed in patients undergoing potentially curative surgery for EC within an enhanced recovery program. OC patients underwent preoperative CPET using automated breath‐by‐breath respiratory gas analysis, with measurements taken during a ramped exercise test on a bicycle. The prognostic value of V ˙ O 2 Peak, Anaerobic Threshold (AT) and VE/VCO2 derived from CPET were studied in relation to post‐operative morbidity, which was collected prospectively, and overall survival. Consecutive 120 patients were included for analysis (median age 65 years, 100 male, 75 neoadjuvant therapy). Median AT in the cohort developing major morbidity (Clavien–Dindo classification >2) was 10.4 mL/kg/min compared with 11.3 mL/kg/min with no major morbidity ( P = 0.048). Median V ˙ O 2 Peak in the cohort developing major morbidity was 17.0 mL/kg/min compared with 18.7 mL/kg/min in the cohort ( P = 0.009). V ˙ O 2 Peak optimum cut‐off was 17.0 mL/kg/min (sensitivity 70%, specificity 53%) and for AT was 10.5 mL/kg/min (sensitivity 60%, specificity 44%). Multivariable analysis revealed V ˙ O 2 Peak to be the only independent factor to predict major morbidity (OR 0.85, 95% CI 0.75–0.97, P = 0.018). Cumulative survival was associated with operative morbidity severity (χ 2 = 4.892, df = 1, P = 0.027). These results indicate that V ˙ O 2 Peak as derived from CPET is a significant predictor of major morbidity after oesophagectomy highlighting the physiological importance of cardiopulmonary fitness. Abstract : V ˙ O 2 Peak was shown to be an important prognostic indicator of major morbidity after oesophagectomy highlighting the physiological importance of cardiopulmonary fitness. CPET has an important role in refining decisions regarding the optimum tailored treatment modality for patients diagnosed with EC as well as planning the appropriate level of postoperative care.